The new quantum universe - Hey, Anthony J. G. (Cambridge University Press, 2003)
This new edition includes a host of new discoveries made in the field of quantum mechanics since 1987. It also looks ahead at the anticipated nanotechnology revolution, describing quantum cryptography, quantum computing & quantum teleportation.